Are Variants Causing Cardiac Arrhythmia Risk Factors in Sudden Unexpected Death in Epilepsy? - Bleakley, Lauren E.; Soh, Ming S.; Bagnall, Richard D.; Sadleir, Lynette G.; Gooley, Samuel; Semsarian, Christopher; Scheffer, Ingrid E.; Berkovic, Samuel F.; Reid, Christopher A. (Frontiers in Neurology, 2020)
Sudden Unexpected Death in Epilepsy (SUDEP) is the most common cause of premature mortality in individuals with epilepsy. Acute and adaptive changes in heart rhythm in epilepsy implicate cardiac dysfunction as a potential pathogenic mechanism in SUDEP. Furthermore, variants in genes associated with long QT syndrome (LQTS) have been identified in patients with SUDEP. LQTS is a cardiac arrhythmia condition that causes sudden cardiac death with strong similarities to SUDEP. Here we discuss the possibility of an additive risk of death due to the functional consequences of a pathogenic variant in a LQTS gene interacting with seizure-mediated changes in cardiac function. Extending this general concept, we propose a hypothesis that common variants in LQTS genes, that cause a subtle impact on channel function and would not normally be considered risk factors for cardiac disease, may increase the risk of sudden death when combined with epilepsy. A greater understanding of the interaction between epilepsy, cardiac arrhythmia and SUDEP will inform our understanding of SUDEP risk and subsequent potential prophylactic treatment.